2004
DOI: 10.1093/carcin/bgh258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYP2A6 genetic polymorphisms as determinants of smoking behavior and tobacco-related lung cancer risk in male Japanese smokers

Abstract: We reported previously that subjects homozygous for the cytochrome P450 2A6 (CYP2A6) (*)4 have a lower risk of lung cancer. The purpose of this study was to clarify whether or not the alterations of smoking behavior and risk for lung cancer could be found in subjects possessing novel CYP2A6 variants discovered recently. An epidemiological study was performed with 1094 cases and 611 controls in male Japanese smokers. It was found that the amounts of daily cigarette consumption in subjects who harbored CYP2A6(*)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
243
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(261 citation statements)
references
References 35 publications
16
243
0
Order By: Relevance
“…178,179 A brief summary of how genetic variations in CYP2A6 affect smoking behaviors will be provided here as a detailed review was recently published. 10 Several studies have associated genetic variations leading to reduced or absent CYP2A6 activity with lower risk of smoking, 175,180,181 decreased cigarette consumption in adults and even in adolescents despite their low smoking rates, 175,[180][181][182][183][184][185][186] decreased smoking intensity, 187 shorter smoking duration, 175 decreased withdrawal symptoms during abstinence 188 and increased cessation. 189 Consistent with this, CYP2A6 inhibition in the presence of 4 mg oral nicotine resulted in higher plasma nicotine levels and reduced smoking (as indicated by decreased breath carbon monoxide levels, numbers of puffs, number of cigarettes smoked and increased latency to next cigarette) during ab libitum smoking.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…178,179 A brief summary of how genetic variations in CYP2A6 affect smoking behaviors will be provided here as a detailed review was recently published. 10 Several studies have associated genetic variations leading to reduced or absent CYP2A6 activity with lower risk of smoking, 175,180,181 decreased cigarette consumption in adults and even in adolescents despite their low smoking rates, 175,[180][181][182][183][184][185][186] decreased smoking intensity, 187 shorter smoking duration, 175 decreased withdrawal symptoms during abstinence 188 and increased cessation. 189 Consistent with this, CYP2A6 inhibition in the presence of 4 mg oral nicotine resulted in higher plasma nicotine levels and reduced smoking (as indicated by decreased breath carbon monoxide levels, numbers of puffs, number of cigarettes smoked and increased latency to next cigarette) during ab libitum smoking.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 99%
“…191,192 Inhibition of CYP2A6 activity in smokers increased clearance of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) glucuronide metabolite, suggesting a decreased metabolic activation of NNK and a shunting of NNK to detoxifying NNAL pathways. 193 The loss-of-function allele (CYP2A6*4) has been associated with a decreased risk of smoking-related cancers, 184,[194][195][196] whereas enhanced CYP2A6 activity, such as the duplication allele (CYP2A6*1X2), is predicted to increase risk.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 99%
“…[21][22][23] In contrast, no clear association was observed in Europeans and Chinese populations. 16,24,25 In those studies, the misgenotyping of the CYP2A6*4 might be one of the possible factors in the contradiction.…”
Section: T Fukami Et Almentioning
confidence: 99%
“…More recently, Schoedel et al 3 concluded that daily cigarette consumption was significantly lower for slow nicotine metabolizers (including CYP2A6*2, CYP2A6*4, CYP2A6*9 and CYP2A6*12 carriers) compared to 'normal' nicotine inactivators (not having any copies of the previously listed alleles) provided that they were nicotine-dependent individuals. Fujieda et al 18 performed an epidemiological study in 1705 Japanese smokers. In their study, subjects carrying CYP2A6*4, CYP2A6*7, CYP2A6*9 and CYP2A6*10 alleles smoked significantly less than subjects with the CYP2A6*1/*1 genotype (combining CYP2A6*1A and CYP2A6*1B).…”
Section: Number Of Cigarettes Smoked Per Daymentioning
confidence: 99%